Identification of information needs in intellectual capital: exploratory study on the Tunisian financial market - Ferchichi, Jihene; Paturel, Robert (International Journal of Accounting and Economics Studies, 2016)
In an economy concretized by the broadening notion of the intellectual capital and its increasing role in investment decisions, it seems appropriate to conceive the intellectual capital by measuring its perception by 22 Tunisian financial professionals. Therefore, the aim of this work consists, firstly, to enable a better understanding of the intellectual capital of the Tunisian financial market. Secondly, by adopting the Delphi method, we determined the information needs and expectations' consensus in terms of intellectual capital. The results from this research show that the concept of intellectual capital appears well known by the financial actors Tunisians. Besides this research, revealed new aspects of intellectual capital. The Tunisian investors consider these dimensions as important criteria that support making their investment decision.Delphi Method; Financial Markets; Informational Needs; Intellectual Capital; Perception.
Keywords: Delphi Method; Financial Markets; Informational Needs; Intellectual Capital; Perception.